Preparation and Identification of Reduced Phosphomolybdate Via, Molybdenum Blue Reaction - Nalumansi, Irene; Birungi, Grace; Moodley, Brenda; Tebandeke, Emmanuel (Oriental Journal of Chemistry, 2020)
Sodium thiosulphate reduced phosphomolybdate (STRP) was prepared based on the condensation of phosphate and molybdate ions in aqueous acid medium to form phosphomolybdic acid (PMA) followed by its reduction to molybdenum blue. The STRP was characterized by ultraviolet-visible spectroscopy, fourier transform infrared spectroscopy, scanning electron microscopy, raman spectroscopy and X-ray powder diffraction. Comparison of spectral data of the STRP to that of the unreduced phosphomolybdate, indicates that the Keggin structure is retained even after reduction. X-ray diffraction data and SEM/EDX results suggest formation of crystalline cubic phosphomolybdate crystals.
Keywords: Phosphomolybdate; Reduction; Molybdenum blue; Keggin structure